Libraries into the 21st century - Dekkers, Makx (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
A long standing colleague discusses developments in informatics in the last quarter century, how these were fostered by the European Commission in general and by Pat Manson in particular.